2019
DOI: 10.3846/jbem.2019.10180
|View full text |Cite
|
Sign up to set email alerts
|

Culture’s Impact on Entrepreneurship and Interaction Effect of Economic Development Level: An 81 Country Study

Abstract: This research has two aims. The first one is to determine how and to what extent the national cultural characteristic of a country plays a role in her entrepreneurship success. The second one is to determine whether culture and economic development levels interact with each other on influencing entrepreneurship success. A consecutive five-year longitudinal study, covering 81 countries is conducted. Longitudinal Random Effect Regression Analysis is used to determine the effects of culture on entrepreneurship ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 67 publications
4
27
0
Order By: Relevance
“…Relatedness is more critical in collectivistic cultures than in individualistic cultures [31]. In addition, China has a high level of masculinity, in which achievement is linked with wealth and status, and the entrepreneurial behavior of an individual is supported [91]. Thus, in entrepreneurship, the support and concern of family and friends conducive to the increment of life satisfaction are more important for Chinese entrepreneurs.…”
Section: National Differences In Life Satisfaction and Entrepreneurshipmentioning
confidence: 99%
“…Relatedness is more critical in collectivistic cultures than in individualistic cultures [31]. In addition, China has a high level of masculinity, in which achievement is linked with wealth and status, and the entrepreneurial behavior of an individual is supported [91]. Thus, in entrepreneurship, the support and concern of family and friends conducive to the increment of life satisfaction are more important for Chinese entrepreneurs.…”
Section: National Differences In Life Satisfaction and Entrepreneurshipmentioning
confidence: 99%
“…It should be noted that culture carries social legitimacy. Therefore, to the extent that a culture values entrepreneurship, it will be highly valued and socially accepted, thus creating a favourable and supportive context for entrepreneurship [45,83,84].…”
Section: Hypotheses and Model Developmentmentioning
confidence: 99%
“…Having a long-term orientation also positively affects the comprehensiveness, speed, and creativity of strategic decision-making processes (Lin et al, 2019). LTO has been found to have a positive influence on the rate of entrepreneurship (Celikkol et al, 2019), which is critical for economic progress. Consistent with this, Gupta et al (2018) showed that long-term orientation is associated with higher IPO activity.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%